Student Consumptive Lifestyle and Its Implications in Guidance and Counseling - Rahmi Azhari; Herman Nirwana; Mega Iswari (Universitas Negeri Padang, 2020)
This study aims to analyze how the form of student's consumptive lifestyle, the factors that cause it, and the negative impact of the student's consumptive lifestyle. This research uses descriptive qualitative method with case study research type. The research subjects were 2 people within the scope of UIN Suska Riau students, using data collection techniques, namely in-depth interviews, observation and documentation. The data analysis technique used by researchers was guided by the Miles & Huberman model. The results showed that the form of a consumptive lifestyle that was seen in the research subjects was excessive shopping and buying goods that did not suit their needs. The contributing factors are shopping because of discounts, likes to be admired by others, and environmental factors. As well as the negative impact of a consumptive lifestyle that occurs on the subject of the study are: low budget economy, likes to lie, becomes a person who likes to be in debt, and is negligent in doing college assignments